THE RELATIONSHIP BETWEEN SELF-CONTROL AND THE TENDENCY OF NO MOBILE PHONE PHOBIA (NOMOPHOBIA) IN ADOLESCENTS AT SMAN 1 BANJARBARU - Rahmah, Mutia; Aisyah, Ririn Noor; Ayatul Azlina, Fitri; Ririn Lestari, Dhian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: Smartphones have become a necessary part of adolescent life. While they offer convenience, excessive use can lead to nomophobia, the fear of being away from smartphones. One of the efforts to overcome nomophobia is self-control. This study aimed to determine the relationship between self-control and the tendency of no mobile phobia (nomophobia) in adolescents at SMAN 1 Banjarbaru. Method: This study used a cross-sectional design. The technique used was stratified random sampling. The research sample amounted to 233 students of SMAN 1 Banjarbaru. The variables were self-control and the tendency of nomophobia (mobile phone phobia). Data were collected by questionnaire and Nomophobia questionnaire and analyzed by Spearman correlation test. Results: The findings revealed that 127 individuals (54.5%) had low self-control, while 126 individuals (54.1%) reported severe nomophobia. The p-value of 0.028 and the coefficient r -0.144 were obtained, indicating a negative relationship between self-control and the tendency of nomophobia among adolescents, with a weak strength of association. Conclusions: There is a relationship between self-control and the tendency for nomophobia (no mobile phone phobia) among adolescents at SMAN 1 Banjarbaru. Further research is needed to explore other factors that may influence nomophobia.